Comparison of opioid local anesthetic combination regimens using the number of self-administrated boluses in patient-controlled epidural analgesia after cesarean section: A retrospective single-center study. Issue 17 (30th April 2021) - Otao, Go; Maruta, Toyoaki; Tsuneyoshi, Isao
Abstract : Abstract: The aim of this study was to assess the efficacy of combined opioids by comparing four regimens of patient-controlled epidural analgesia (PCEA) after cesarean section. Parturient patients who underwent elective or emergent cesarean section under combined spinal and epidural anesthesia from April 2013 to March 2016 were retrospectively analyzed. Based on PCEA, they were assigned to one of 4 groups: local anesthetic alone (LA), epidural single morphine administration during surgery followed by local anesthetic alone (M), local anesthetic combined with fentanyl 10 μg/h (F10), or local anesthetic combined with fentanyl 20 μg/h (F20). The primary outcome was the number of PCEA boluses used. Secondary outcomes included the use of rescue analgesia, postoperative nausea and vomiting, and postoperative pruritus. A total of 250 parturients were analyzed. Whereas the number of PCEA boluses in the LA group was significantly higher than in the other combined opioid groups on the day of surgery and postoperative day 1 (LA: 3 [1–6] and 7 [4–9] vs M: 2 [0–4] and 4 [0–7] vs F10: 1 [0–4] and 3 [0–6] vs F20: 1 [0–3] and 2 [0–8], P  = .012 and 0.010, respectively), within the combined opioid groups, the number was not significantly different. Significantly fewer patients in the F20 group required rescue analgesia on postoperative day 1 and 2 (25 and 55%) than those in the M (66 and 81%) and F10 (62 and 66%) groups ( P  < .001 and P = .007, respectively). Postoperative nausea and vomiting and pruritus were significantly higher in the M group ( P  < .008 and P = .024, respectively). The results of the present study suggest that local anesthetic alone after a single administration of morphine, or local anesthetic combined with fentanyl 10 μg/h would generally be adequate for PCEA, whereas local anesthetic combined with fentanyl 20 μg/h would be suitable for conventional epidural analgesia.